2000
DOI: 10.1016/s0002-9440(10)64543-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Heterozygosity in Fibrocystic Change of the Breast

Abstract: Loss of heterozygosity (LOH), a genetic change frequently detected in cancer, can also occur in benign epithelial foci in the breast. To characterize LOH in benign breast tissue, 32 cases containing the various components of fibrocystic change in the absence of malignancy were studied. Microdissected foci of ductal hyperplasia, apocrine metaplasia, sclerosing adenosis, and morphologically normal terminal duct lobular units (TDLUs) were analyzed for LOH at 14 polymorphic loci representing seven chromosomal arms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(12 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…However, although LOH is observed in UDH, the pattern of LOH is notably different from that associated with ADH and DCIS (75, 83-88). More specifically, only rare and fairly randomly distributed chromosomal changes, or no changes at all, occur in UDH (a pattern similar to that observed in phenotypically normal breast tissue and nonproliferative fibrocystic change), whereas recurrent, nonrandomly distributed chromosomal changes (in particular 16q loss) occur more frequently in ADH and DCIS (69, 75, 85, 86, 88-90). Taken together, these observations support the role of FEA as the precursor to ADH.…”
Section: Gene-expression Analysis Of Invasive Ductal Carcinomamentioning
confidence: 54%
“…However, although LOH is observed in UDH, the pattern of LOH is notably different from that associated with ADH and DCIS (75, 83-88). More specifically, only rare and fairly randomly distributed chromosomal changes, or no changes at all, occur in UDH (a pattern similar to that observed in phenotypically normal breast tissue and nonproliferative fibrocystic change), whereas recurrent, nonrandomly distributed chromosomal changes (in particular 16q loss) occur more frequently in ADH and DCIS (69, 75, 85, 86, 88-90). Taken together, these observations support the role of FEA as the precursor to ADH.…”
Section: Gene-expression Analysis Of Invasive Ductal Carcinomamentioning
confidence: 54%
“…While a restored normal tissue context may suppress or inhibit malignant transformation (Stoker et al, 1990;Javaherian et al, 1998;Bissell et al, 1999;Hsu et al, 2000b;Olumi et al, 1999;Stoler et al, 1999;Frame and Balmain, 2000;Washington et al, 2000), activated stroma could function as a tumor promoter (Mintz and Silvers, 1993;Thomasset et al, 1998;Barcellos-Hoff and Ravani, 2000;Moinfar et al, 2000;Li et al, 2001a;Tlsty, 2001; Satyamoorthy et al, Figure 6 Proposed sources of fibroblasts in melanoma stroma. Activated fibroblasts in melanoma stroma may be derived from either the resident pool in the dermis, or from bone marrow-derived circulating mesenchymal stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence exists that restored normal context could suppress the transformed phenotype (Javaherian et al, 1998;Olumi et al, 1999;Hsu et al, 2000b) and lead to inhibition or even reversion of tumors in situ (Stoker et al, 1990;Deng et al, 1996;Bissell et al, 1999;Stoler et al, 1999;Frame and Balmain, 2000;Washington et al, 2000). For example, when normal Mc are isolated from skin and then cultured, they display a bi-or tripolar morphology, and express cell surface molecules that are only found on melanoma cells in situ (ValyiNagy et al, 1993).…”
mentioning
confidence: 99%
“…This equilibrium might attenuate the consequences of genetic mutations, as consideration of the frequency of spontaneous mutations indicates that many epithelial cells should possess oncogene-activating mutations, yet cells continue to function normally 30,31 . Analyses of normal epithelial tissue adjacent to tumours have shown that similar patterns of mutations can be found in both, indicating that malignant cells can exist within normal tissues but be restrained by normal contextual cues [32][33][34] .…”
Section: Box 1 Epithelial Cell Polarity and Tumorigenesis In Drosophilamentioning
confidence: 99%